2020
DOI: 10.21203/rs.3.rs-123999/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of combination treatment using YHO-1701, an orally active STAT3 inhibitor, with molecular-targeted agents on cancer cell lines

Abstract: Signal transducer and activator of transcription 3 (STAT3) plays a critical role in regulating cell growth, survival, and metastasis. STAT3 signaling is constitutively activated in various types of hematologic or solid malignancies. YHO-1701 has been developed as an orally available STAT3 inhibitor. Herein, YHO-1701 in combination with molecular-targeted agents was evaluated. Additive or synergistic effects were observed in a broad spectrum of “combination treatment + cell line” pairs. Of particular interest w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Previous investigations have revealed synergy of ALK inhibitors with other classes of drug in cells expressing EML4-ALK fusions. For example, dasatinib (an ABL and SRC kinase inhibitor) produced a synergistic response with crizotinib in both H3122 and H2228 cells (37), whereas a STAT3 inhibitor, YHO-1701, exhibited synergy with alectinib, crizotinib, and ceritinib in H2228 cells (38). Other studies have found ceritinib and paclitaxel to be highly synergistic in the treatment of lung cancer cells with activation of the FAK even if they do not express EML4-ALK fusions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have revealed synergy of ALK inhibitors with other classes of drug in cells expressing EML4-ALK fusions. For example, dasatinib (an ABL and SRC kinase inhibitor) produced a synergistic response with crizotinib in both H3122 and H2228 cells (37), whereas a STAT3 inhibitor, YHO-1701, exhibited synergy with alectinib, crizotinib, and ceritinib in H2228 cells (38). Other studies have found ceritinib and paclitaxel to be highly synergistic in the treatment of lung cancer cells with activation of the FAK even if they do not express EML4-ALK fusions (39).…”
Section: Discussionmentioning
confidence: 99%
“…In nude mice, alectimib at a dose of 6 mg/kg significantly inhibited the growth of NCI-H2228 and KARPAS -299 cell transplantation tumors. In terms of the ability to overcome mutations, 100nM alectimib inhibited the phosphorylation of ALK in BaF3/EML4-ALK -L1196M cells [93,94]. 3) Brigatinib Brigatinib is a dual target inhibitor of ALK and epidermal growth factor receptor (EGFR).…”
Section: Alk Inhibitorsmentioning
confidence: 99%